A Case of Anagrelide-Induced Nonischemic Cardiomyopathy in a Patient With Essential Thrombocythemia. (April 2018) - Singh, Pritpal
Background: Anagrelide is an established treatment option for essential thrombocythemia (ET). Cardiovascular adverse events can occur with its use including heart failure and cardiomyopathy. Case Report: A 52-year-old African American male with ET presented with chest pain, shortness of breath, and dyspnea on exertion. His ET was managed with hydroxyurea 1500 mg by mouth twice a day and anagrelide 1 mg by mouth 3 times a day. The patient was receiving anagrelide for approximately 2 years prior to presentation. The patient's platelet count was 2.07 × 10 5 cells/mm 3 . Transthoracic echocardiography revealed decreased left systolic dysfunction. Also, cardiac magnetic resonance imaging showed an increased left ventricle cavity size with severely depressed systolic dysfunction and an ejection fraction (EF) of 18%. Anagrelide therapy was discontinued and the patient was maintained on hydroxyurea for ET. Three months later, following treatment by a heart failure clinic, the patient's EF was 55%. Five months after discontinuation, the patient improved from New York Heart Association (NYHA) class II to NYHA class I. Conclusion: A 52-year-old man with ET presented with an EF of 18% after 2 years of anagrelide therapy. His EF increased from 18% to 55% 3 months after discontinuation of anagrelide.